Pengaruh Customer Relationship Marketing Terhadap Kepuasan Dan Loyalitas Merchant Partner Grab Food di Kota Pekanbaru - Ricky Purnama Sanjaya; Zulkarnain Zulkarnain; Samsir Samsir (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to determine the effect of Customer Relationship Marketing on Satisfaction and Loyalty of Grab Food Merchant Partners in Pekanbaru City. The population taken from this research is Grab Food merchant partner in Pekanbaru. The method used in this research is descriptive quantitative method. And testing the hypothesis in this study using the analysis of Structural Equation Modeling (SEM). The data collection technique was done by interview and questionnaire. The results of this study indicate that from the variable Customer Relationship Marketing (Trust, Commitment, Communication and Problem Handling), variables of trust and problem handling have a positive but insignificant effect on the satisfaction of merchant partners. Meanwhile, Commitment and Communication have a positive and significant effect on merchant partner satisfaction. Then the results of this study also show that the Satisfaction variable has a positive and significant effect on the Loyalty of Grab Food partner merchants in Pekanbaru.